Surface prereacted glass-ionomer particles incorporated into resin composites promote biocompatibility for restoration of subgingival dental defects - Yueyi Yang; Jing Huang; Xuchen Hu; Meiling Jing; Yujie Zhang; Chenci Xu; Wenduo Tan; Xiaoyu Liu; Chenguang Niu; Zhengwei Huang (Materials Today Bio)
Subgingival dental defects are common in clinical practice among patients with deep dental caries and dental fractures. These defects commonly accompany lesions involving marginal alveolar bone loss and gingival recession, and their clinical management is challenging. Restoring gingival adhesion and activating the regeneration of periodontal tissue are important for a better prognosis in these cases. However, there is no effective resin material for complex restorations involving the destruction of subgingival tissue. To achieve greater biocompatibility, resins are generally modified with bioactive particles that can release specific components. Surface prereacted glass ionomer (S-PRG) is a novel glass particle characterized by a three-layered structure and the release of multiple ions with bioactive potential. Therefore, in this study, we incorporated S-PRG filler into resin-based composites to investigate their effectiveness in the restoration of subgingival defects. Resin composites containing 0, 10, 30, 50, or 70 wt% S-RPG filler were fabricated and formed into material discs, where a commercial resin composite served as the control group. The microstructure and elemental distribution were characterized by scanning electronic microscopy and energy-dispersive spectroscopy. The resin composites containing 50 or 70 wt% S-PRG fillers exhibited comprehensively better physicochemical properties, including flexural modulus, compressive strength, and water sorption. The ion release profile and environmental pH of the resins were measured with material extracts. Periodontal ligament stem cells were considered as seed cells that harbored great potential for periodontal regeneration. Cellular experiments suggested that S-PRG promotes cell proliferation and adhesion, induces cell migration, and stimulates vascularized osteogenesis. The feasibility of using S-PRG-containing resin composite to rectify subgingival dental defects was confirmed in vivo. After restoration with the S-PRG-filled resin material, intact epithelial tissue adhered to the resin surface with no visible inflammation. In conclusion, S-PRG-filled resin composites showed some biocompatibility as an alternative material for clinical applications.